2011
DOI: 10.3390/ijms12095797
|View full text |Cite
|
Sign up to set email alerts
|

Role of α-Helical Structure in Organic Solvent-Activated Homodimer of Elastase Strain K

Abstract: Recombinant elastase strain K overexpressed from E. coli KRX/pCon2(3) was purified to homogeneity by a combination of hydrophobic interaction chromatography and ion exchange chromatography, with a final yield of 48% and a 25-fold increase in specific activity. The purified protein had exhibited a first ever reported homodimer size of 65 kDa by SDS-PAGE and MALDI-TOF, a size which is totally distinct from that of typically reported 33 kDa monomer from P. aeruginosa. The organic solvent stability experiment had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Elastase strain K is an organic solvent tolerant protease that is isolated from Pseudomonas aeruginosa strain K, wherein the organic solvent tolerant protease exhibits stability and enhanced activity in a wide range of polar organic solvents. In Rahman et al, recombinant elastase strain K had previously shown stability in 25% (v/v) polar organic solvents such as ethanol, methanol, 1-propanol, and DMSO [14][15][16]. The ability of elastase strain K to withstand a broad range of organic solvents allows it to be applied in the enzyme industry and to be run through extreme processes.…”
Section: Introductionmentioning
confidence: 99%
“…Elastase strain K is an organic solvent tolerant protease that is isolated from Pseudomonas aeruginosa strain K, wherein the organic solvent tolerant protease exhibits stability and enhanced activity in a wide range of polar organic solvents. In Rahman et al, recombinant elastase strain K had previously shown stability in 25% (v/v) polar organic solvents such as ethanol, methanol, 1-propanol, and DMSO [14][15][16]. The ability of elastase strain K to withstand a broad range of organic solvents allows it to be applied in the enzyme industry and to be run through extreme processes.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect of divalent ions, such as Zn 2+ and Ni 2+ , was clearly observed on aminoacylase SZN. These ions have been reported to inhibit the proteolytic activities of elastase strain K (Rahman et al, 2011), ME-4 (Cheng et al, 2009) and PseA (Gupta et al, 2005) which also happened to be metalloproteases. The highest half-life of aminoacylase was reported by Hollingsworth (2002), who found that the stability of aminoacylase from Thermococcus litoralis was 25 h at 70°C.…”
Section: Discussionmentioning
confidence: 98%
“…Our results showed that 1 mM metal ion reduced the aminoacylase activity, whereas the 10 mM Cu 2+ Mg 2+ , Mn 2+ and Na + increased the aminoacylase activity to 107, 153, 160 and 136%, respectively (Supplementary Material 2c). We postulate that increased concentration of divalent ions, such as Mg 2+ and Mn 2+ , may result in enhancement of activity, probably due to increased stability in enzymesubstrate and product complexes (Knape et al, 2017;Rahman et al, 2011).…”
Section: Effect Of Metal Ions On Aminoacylase Activitymentioning
confidence: 93%
“…The recombinant elastase strain K was overexpressed in E. coli KRX/pCon2(3) and purified to homogeneity as described by Rahman et al [11] with slight modifications. Three liters of E. coli KRX/pCon2(3) culture was harvested through centrifugation and the precipitated cells were dissolved in reaction buffer (50 mM Tris-Cl, pH 8.5) before sonication to release the enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…Exploring the stability of this enzyme (elastase from P. aeruginosa strain K) and using molecular genetics for gene overexpression were well documented by Wong et al [10]. Further investigations to characterize the purified recombinant elastase strain K showed its capability for activity in hydrophilic organic solvent media [11]. Given the previous investigations, our research will focus on recombinant elastase strain K crystallization and structure determination to discern its structural features as an organic solvent-stable enzyme.…”
Section: Introductionmentioning
confidence: 99%